An innovative approach of 3D printed functional foods: Grasshoppers based cookies - Su, Sena; Pilavci, Esra; Yesiloz, Simal Erva; Demir, Aysegul Uzuner; Sancakli, Aykut; Gunduz, Sema; Kibar, Emine Aytunga Arik; Bahar, Mesude Banu; Gunduz, Oguzhan (ELSEVIER, 2025)
Supplements can be used to enhance the nutritional properties of food. Combining these supplements with 3D printing technology has the potential to increase food variation by facilitating food processibility. In this paper, we provide some trailblazing examples to develop protein-rich cookies using 3D printing as a processing method to support sustainable food sources and to reduce prejudice towards edible insects. The cookies were printed in 3 groups as: tasteless(T), salty(S1) and sugary(S2). Freeze drying was used as post-process to extend the shelf life of the cookies and provide a crispy structure. Printability and the effects of salt and sugar addition on the rheological properties of the grasshopper powder-added paste were investigated. The printed cookie samples were characterised by Fourier transform infrared spectroscopy (ATR-FT-IR), Scanning electron microscopy (SEM), texture measurements, nitrogen content and crude protein determination, colour analysis and sensory analysis. Rheology analysis revealed that S1 and S2 pastes exhibit an elastic behaviour as a solid material (G' > G '') while the T paste exhibits a viscous behaviour as a liquid (G > G'). Quantitative printability testing by examining the pore structure of 3D-printed cookies confirmed that all pastes were printable in high quality. Characteristic peaks of grasshopper powder were detected for each cookie according to chemical evolution. Morphological analysis demonstrated that grasshopper powder was encapsulated into the cookies. Moreover, the surface of the T and S2 samples was close to a smoother appearance, but more cracks were observed on the surface of the S1 cookie related to the salt content. According to the crude protein test results, it was seen that cookies with high protein content were produced (25.00% +/- 0.35 for sample T). Colour analysis showed that there were no significant differences between samples. Textural evaluation showed that salt and sugar added increased the hardness, adhesiveness, springiness, cohesiveness, and resilience. Sensory analysis attributes of the sugar-added product is the most preferred sample according to crispiness, flavour and overall preference criteria than the other two samples. The results of this study demonstrated that production with integration of 3D printing and freeze-drying technology can produce a shelf-stable snack food as a supplement product.
Keywords: 3D food printing; Edible insects; Grasshopper; Rheology; Sensory analysis; COLOR MEASUREMENT; PROTEIN; CONSUMPTION; TECHNOLOGY; GELATIN; INSECTS; TEXTURE; Food Science & Technology